NURSING CARE IN TN S WITH MEDICAL DIAGNOSIS GOUT ATHTRITIS THE MAIN PROBLEM OF ACUTE PAIN AT THE SOCIAL SERVICE CENTER OF THE DEWANATA CILACAP - Melinda Melinda; Wasis Eko Kurniawan (Bajang Institute, 2022)
The older a person is, they will experience a decline, especially in physical abilities. This of course causes the elderly to be susceptible to various disease disorders, one of which is a disease that often affects the elderly, namely gout. Nursing care is also important to overcome the disorder Arthritis Gout. One of the treatments for Arthritis Gout patients is to reduce pain in the joints by reducing the intake of foods rich in purines (eg crotch, mental stress (stress), due to infection or side effects of certain drugs). Preventing complications, reducing the risks and improving the patient's health comprehensively is the nurse's duty to provide nursing care. The aim of the research is to be able to provide nursing care to Mrs. r with a medical diagnosis of gout arthritis, the main problem is acute pain at the Dewanata Social Service Center, Cilacap. This research method uses a descriptive case study design. In this case study, the subject is Mr. S with acute pain problems. The results show that the author makes a nursing care plan for Mr. S which includes and is adapted to the patient's condition. Evaluation of the results of nursing care for Mr. S with acute pain has been resolved, marked by a relaxed facial expression and a pain scale of 1 out of 10, so the risks that may arise do not occur.